PENGGUNAAN ANJING PELACAK DALAM MENGUNGKAP TINDAK PIDANA PENGANIAYAAN YANG MENYEBABKAN MATINYA ORANG DI WILAYAH HUKUM POLRES SOLOK SELATAN (Studi tentang Koordinasi antara Penyidik Polres Solok Selatan dengan Direktorat Samapta Polda Sumatera Barat Dala - Jumantri, Randi (Universitas Ekasakti, 2021)
The first step in an investigation itself is to find items in a criminal case which are items indicated as evidence of a crime that was found left behind at the scene of the crime or abbreviated as TKP. In a crime case that resulted in the death of a person, the Animal Unit of the Samapta Bhayangkara Directorate of the West Sumatra Police was asked to provide assistance with sniffer dogs by the South Solok Police Criminal Investigation Unit regarding a serious case that resulted in the death of the victim that occurred in the Solok Police Legal Area. With Police Report No. Pol : LP/138/X/2018/Spkt–Pagu Police, 01 October 2018.